(untitled) (Revista de História Regional, 2020)
This article is a contribution to the regional history of Brazil and the history of the Amazon, with the objective of analyzing how provincial themes were transformed into regional and national issues in the northern parliamentary discourse, seeking to examine in this process how a transition was taking place in the way of conceiving space, by the political representatives of the North on the banks of the Amazon River. For the writing of the article were used as main documents the Anais of the Brazilian Parliament, in addition to other sources, such as newspapers, reports and collections of parliamentary speeches.